Safety of the treatment with retinoids - Żaba, Ryszard (Przewodnik Lekarza/Guide for GPs, 2006)
The purpose of this paper was to evaluate mechanism of action, efficacy, tolerability and side effects linked to the treatment of some diseases with administration of various retinoids applied locally and/or systemic. Systemic and topical retinoids has been used to treat severe acne vulgaris and many other diseases. Oral retinoids are the most effective class of drugs for many disorders of cornification. Retinoids are also involved in the regulation of diverse biologic functions, among others cellular growth, differentation, alter cellular cohesiveness, and morfogenesis. As with other medications, a risk/benefit ratio should be used to determine whether or not to treat a dermatologic patient with synthetic retinoids.